A mini review on characteristic of depik fish (Rasbora tawarensis) and its processed products. Issue 1 (January 2021) - Rahmi, F; Susanti, Z; Nilda, C; Muzaifa, M
Abstract: Depik fish ( Rasbora tawarensis ) is a tpical endemic freshwater fish of Laut Tawar Lake in Central Aceh, Aceh Province. This lake has become the pride of the Gayo community as a source of clean water for various needs, a source of livelihood for residents and a tourist destination. Laut Tawar Lake and depik fish have become the trademark of the city of Takengon, Central Aceh. However, it is unfortunate that due to several reasons such as environmental degradation, introduction of foreign fish, destructive fishing techniques, pollution and climate change globally, depik fish population is currently decreasing drastically. Even depik fish has been appointed as a fish with a threatened status. Studies on the existence of depik fish as local food, form of presentation and nutrition are still rarely carried out. This article tries to review the existence of depik fish and its processed products through several existing studies including classification, distribution, morphological and genetic characteristics of depik fish as well as processing and characteristics of processed products.